Changing Police Officers’ Attitudes in Sexual Offense Cases: A 12-Month Follow-Up Study - Tidmarsh, Patrick (Criminal justice and behavior, 2020)
We examined whether specialist training can have an immediate and lasting impact on investigators’ attitudes in sexual offense cases. Australian police officers participated in a 4-week training program that focused on the dynamics of sexual offending. Officers completed questionnaires before, immediately after, and 9 to 12 months following training. They were presented with scenarios involving adult and child complainants with varying levels of evidence (strong, weak, or ambiguous) and rated their confidence that the case would be approved for prosecution, the likelihood of a guilty verdict, and the level of responsibility attributed to the victim. Following training, investigators became more confident in case approvals and guilty verdicts, less likely to attribute responsibility to victims, and demonstrated better understanding of sexual offense dynamics. Ratings of victim responsibility and guilty verdicts were maintained 9 to 12 months post-training; however, confidence in case approvals decreased after working in the field. Implications for police training programs are discussed.